Creep-feed grinding - Grigoriev, Sergey N. (Strojniški vestnik, 2014)
Grinding kinematics is one of the main mechanisms affecting the behaviour and efficiency of the creep-feed grinding process; it is thus essential in understanding the interplay of its parameters in the material removal. This paper presents an overview of non-traditional process parameters, such as the apparent area of the removed material, the grinding force engagement angle, the ratio of normal-to-tangential grinding force, as well as the ratio between the depth of cut and the wheel diameter. The kinematic aspects of creep-feed grinding processes are illustrated in three different case studies for creep-feed grinding of turbine blades, gears and broaches, using highly porous, vitrified, alumina-oxide wheels at low speeds. Details about the experimental work, especially with regard to analysis and validation, are not included. Based on the case studies, however, some practical guidelines for improving process efficiency in terms of productivity and quality are provided.
Keywords: globoko brušenje; kinematika brušenja; konvencionalni abrazivi; parametri